The effect of the SQUIRE (Standards of QUality Improvement Reporting Excellence) guidelines on reporting standards in the quality improvement literature: a before-and-after study. Issue 6 (12th February 2015) - Howell, Victoria; Schwartz, Amanda Eva; O'Leary, James Daniel; Donnell, Conor Mc
Abstract : Background: The SQUIRE (Standards of QUality Improvement Reporting Excellence) guidelines were developed to improve the reporting of quality improvement (QI) projects. The effect of the guidelines on the completeness of reporting in the QI literature is unknown. Objectives: Our primary objective was to determine if the completeness of reporting in the QI literature has been improved[OUP_CE13] since the introduction of the SQUIRE guidelines. Methods: We performed a before-and-after evaluation of QI articles selected from four prominent journals of healthcare quality. Twenty-five articles published in each of two time periods (2006–2008 and 2010–2011) were confirmed to be QI projects using a standardised definition and were independently evaluated by two investigators as an interim evaluation of a planned larger sample. Articles were assessed using 50 statements of the SQUIRE guidelines, and the overall change in the completeness of reporting between the two groups was determined. The value of p<0.05 was considered significant. Results: Both groups were similar in characteristics. There was no significant difference in the mean (SD) number of SQUIRE statements completed by authors before and after publication of the SQUIRE guidelines, 20.2 (5.0) versus 20.4 (7.0), p=0.9. The study was stopped early due to the absence of any significant trend in the completeness of reporting. Discussion: There was no overall improvement observed in the completeness of reporting of QI projects after the publication of the SQUIRE guidelines, and the study was stopped early. There is potential for improvement in reporting standards, particularly for those guideline items or statements specific to QI projects.